Suppression of mRNA Nanoparticle Transfection in Human Fibroblasts by Selected Interferon Inhibiting Small Molecule Compounds - Liu, Yang (Biomolecules, 2017)
In vitro transcribed (IVT) mRNA is increasingly applied in lieu of DNA to deliver reprogramming genes to fibroblasts for stem cell derivation. However, IVT mRNA induces interferon (IFN) responses from mammalian cells that reduces transfection efficiency. It has been previously suggested that small molecule inhibitors of IFN are a viable strategy to enhance mRNA transfection efficiency. Herein, we screen a list of commercially available small molecules, including published IFN inhibitors, for their potential to enhance mRNA transfection in BJ fibroblasts. Transfection enhancement is quantified by relative mean fluorescence intensity of translated green fluorescent protein (GFP) in treated cells compared to dimethyl sulfoxide treated controls. Within toxicological constrains, all tested small molecules did not enhance mRNA transfection in BJ fibroblasts while a third of the tested compounds unexpectedly inhibited GFP expression even though IFN-β production is inhibited. Based on the results of our study, we conclude that small molecule inhibitors, including IFN inhibitors, tested in this study do not enhance in vitro mRNA transfection efficiency in human fibroblasts.